Zakres znaczeniowy określenia „akty i czynności z zakresu administracji publicznej” w rozumieniu art. 3 § 2 pkt 4 Prawa o postępowaniu przed sądami administracyjnymi - Maciejko, Marek (Kwartalnik Prawa Publicznego, 2017)
It was in 1995 that a possibility was created in Polish legislation that enabled to sue decisions and rulings from the area of public administration. Such a term had never before existed in the language of normative acts. As far as the term “activity” is known in the common parlance, the term “administrative act” has no determined meaning in common, everyday language. Because it is necessary to understand the legal regulations clearly and precisely, it is essential to refer to writings and judicial decisions up to date. Such analysis is presented in this paper. A conclusion is offered which states that the use of unknown expression, which was not used in legislation nor in extra-legal language, leads to inconsistency in judicial decisions. This, in turn, generates further interventions on the part of the legislator who tries to precise the term with reference to selected areas of administrative activity. In reality, instead of helping to understand the term, they make it even more complicated and increase the conceptual chaos. Finally, a conclusion de lege ferenda is offered which postulates a definition of an administrative act: “An administrative act is every legally binding expression of an administrative organ or another entity which performs activities in the area of public administration.” A proposal is also presented which aims at defining activities from an area of public administration by offering a sampled catalogue of activities which is not comprehensive. This would facilitate the work of an interpreter, although such definition is not as necessary as in the case of administrative acts.